EVALUASI PROGRAM ADIWIYATA (SEKOLAH BERWAWASAN LINGKUNGAN) DI SD NEGERI 44 PEKANBARU - Dody Ariyadi; Isjoni Isjoni; Daeng Ayub Natuna (Universitas Riau, 2018)
This study is a qualitative study that aimed to evaluate Adiwiyata in SD Negeri44 Pekanbaru. This study focuses on the evaluation of Adiwiyata in SD Negeri 44 Pekanbaru.Subfocus this study consisted of 1) The target precision program implementation Adiwiyata inSD Negeri 44 Pekanbaru, 2) System management used by the Principal of SD Negeri 44Pekanbaru in Adiwiyata, 3) The Form of activities in Adiwiyata in SD Negeri 44 Pekanbaru, 4)The success rate of the program implementation Adiwiyata in SD Negeri 44 Pekanbaru, 5)supporting and inhibiting factors Adiwiyata in SD Negeri 44 Pekanbaru. This research datacollection through interviews, observation and documentation with goal attainment modelapproach models of the evaluation model goals. The results showed that the subfocus targetprecision Adiwiyata in SD Negeri 44 Pekanbaru already are in the category of very effective,subfocus management system used by the principal to Adiwiyata in SD Negeri 44 Pekanbaru isquite effective done, on subfocus forms of activities Adiwiyata in SD Negeri 44 Pekanbaru alsobeen performing well and are in the category of very effective, then the subfocus successAdiwiyata SD Negeri 44 Pekanbaru also been performing well and are in the category of veryeffective while at subfocus supporting factors and factors inhibiting the implementation of theprogram Adiwiyata SD Negeri 44 Pekanbaru because they found the inhibiting factors in thecategory quite effective. It can be seen that for Adiwiyata students at SDN 44 Pekanbaruoverall and subfocus aspects of research can be said to have been effective because there aretwo of five subfocus subfocus categorized as highly effective and three subfocus categorizedquite effective.